Global or embedded service work? the (limited) transnationalisation of the call-centre industry. (1st July 2009) - Ursula Holtgrewe; Jessica Longen; Hannelore Mottweiler; Annika Schönauer
Abstract : This paper explores the amount of 'real' internationalisation in the call centre industry and looks at its effects on work organisation from two angles. First, we analyse the data from the Global Call Center Industry Project, with regard to the amount of internationalisation and the profiles of call centres serving an international market. Then, these industrywide findings are confronted with a case study of the customer service operation of a US-based electronics multinational. Overall, while global business service providers exist and shape the perception of the industry to a considerable extent, internationalisation is chiefly limited to younger, larger subcontracting companies with standardised work, although national patterns vary. While some services in some segments have certainly been internationalised (for example airline travel reservations and IT helplines), language and cultural proximity continue to matter.